2009
DOI: 10.1016/j.immuni.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Conformations of Ly49 Natural Killer Cell Receptors Mediate MHC Class I Recognition in Trans and Cis

Abstract: Summary Certain cell surface receptors engage ligands expressed on juxtaposed cells, but also ligands on the same cell. The structural basis for trans versus cis binding is not known. Here, we show that Ly49 natural killer (NK) cell receptors bind two MHC class I (MHC-I) molecules in trans when the two ligand-binding domains are back-folded onto the long stalk region. In contrast, dissociation of the ligand-binding domains from the stalk and their reorientation relative to the NK cell membrane allow monovalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 31 publications
6
89
0
Order By: Relevance
“…The protein was produced as described for Ly49L (21). Briefly, Ly49H was expressed in Escherichia coli BL21(DE3) as inclusion bodies; solubilized in 6 M guanidine; and folded in vitro by dilution into 30% (v/v) glycerol, 0.4 M arginine, 50 mM Hepes (pH 7.0), 100 mM NaCl, 3 mM reduced glutathione, and 0.8 mM oxidized glutathione.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The protein was produced as described for Ly49L (21). Briefly, Ly49H was expressed in Escherichia coli BL21(DE3) as inclusion bodies; solubilized in 6 M guanidine; and folded in vitro by dilution into 30% (v/v) glycerol, 0.4 M arginine, 50 mM Hepes (pH 7.0), 100 mM NaCl, 3 mM reduced glutathione, and 0.8 mM oxidized glutathione.…”
Section: Methodsmentioning
confidence: 99%
“…Considerable structural information is available for Ly49 receptors in MHC-bound and unbound forms. Crystal structures have been reported for Ly49A NKD in complex with H-2D d (16,17), Ly49C NKD bound to H-2K b (18,19), Ly49C NKD (19), Ly49I NKD (20), Ly49G2 NKD (19), Ly49L NKD (21), and Ly49L NKD with the stalk region (21). Collectively, these studies have shown that Ly49 receptors can adopt two distinct conformations: 1) a backfolded conformation in which the NKDs of the Ly49 dimer are backfolded onto the helical stalk region (Fig.…”
Section: Natural Killer (Nk)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is referred to as cis interaction, whereas binding to MHC-I on another cell is a trans interaction. Cis and trans interactions have two distinct receptor conformations made possible due to the flexible stalk; the stalk is able to bend into a back-fold conformation allowing for trans binding and straightens into an extended conformation for cis interactions (18). Cis interactions are stable and sequester Ly49A so that most receptors are not available for MHC-I binding in trans (19).…”
mentioning
confidence: 99%